(untitled) (Research, Society and Development, 2023)
Introduction: Bisphosphonates (BPs) are currently the most relevant class of antiresorptive agents used in the treatment of bone pathologies, such as multiple myeloma, bone metastases, Paget’s bone disease, osteogenesis imperfecta and osteoporosis. The mechanism of action of these drugs reduces the lifetime and function of osteoclasts, interfering with the bone remodeling process. In addition, they also promote inhibitory effects on inflammation mediators, which influence the bone repair process. Therefore, when used in association with dental surgical interventions, there is an increase in postoperative complications, since one of the steps for bone repair is remodeling, which is affected by bisphosphonates. The complications resulting from its use came to be called Osteonecrosis of the Jaws related to bisphosphonates. Objective: This paper aims to report the case of a female patient, 70 years old, with osteoporosis and systemic arterial hypertension, who uses sodium alendronate bisphosphonate (Osteoform®). The patient attended the Oral Surgery Clinic at Faculdade Paulo Picanço in need of extraction of the residual root of element 45, and underwent the surgical procedure. The procedure was performed under antibiotic coverage followed by laser therapy sessions. The patient was followed up for a period of 6 months, aiming to guarantee a good prognosis. Final considerations: Bisphosphonates (BFs) are first-choice drugs for various bone pathologies and their use is increasingly frequent. Preventive treatment plays a key role in reducing the chances of bisphosphonate-related Osteonecrosis of the Jaws (BMB). Currently, there are still no defined therapeutic dental protocols for the treatment of OMB, which emphasizes the importance of prevention as the best option in coping with this condition. Dental care prior to starting therapy with antiresorptive drugs is essential and should be an integral part of the treatment plan for patients who will use these drugs.